PERLINDUNGAN HUKUM PADA SAKSI PENANGANAN PELANGGARAN PEMILU (Jurnal Huma Betang Demokrasi, 2021)
Legal protection is a form of service that must be provided by the government to provide a sense of security to every citizen. Based on the Constitution of the Republic of Indonesia (hereinafter referred to as the 1945 Constitution of the Republic of Indonesia). The implementation of the election itself cannot be separated from the violations that occurred. One of the most important roles in handling election violations is the witness. The importance of legal protection for every community is one of the reasons for the issuance of Law Number 31 of 2014 concerning Amendments to Law Number 13 of 2006 concerning Protection of Witnesses and Victims. It also regulates an institution that is responsible for handling the provision of protection and assistance to witnesses and victims, called the Witness and Victim Protection Agency (LPSK). Therefore, the role of the LPSK includes the protection of witnesses in handling election violations.Protection of witnesses handling election violations can apply for protection in accordance with the protection mechanism by LPSK, the mechanism for handling election violations that has been regulated is a way for LPSK to provide protection according to the applicable rules in the form of their rights and obligations as witnesses in handling violations. Witnesses in handling election violations must be treated in a balanced way between their rights and obligations. The provision of witness protection during election crimes is provided with two protection models, namely a combination of the procedural rights model and the service mode.
Keywords: Protection; Witness; Election Violations